PERBANDINGAN PENURUNAN KADAR KOLESTEROL PADA PASIEN HIPERKOLESTEROLEMIA ANTARA TERAPI AKUPUNKTUR PADA TITIK ST 36, ST 40, SP 6 DAN RN 12 DENGAN KOMBINASI HERBAL GINGSENG MERAH - Sri Yatmihatun; Kurnia Eka Putri (Rena Cipta Mandiri, 2025)
This study aims to compare the effectiveness of acupuncture therapy and red ginseng herbal combination in reducing cholesterol levels in hypercholesterolemia patients. A Randomized Controlled Trial design with a two-group pretest-posttest approach was applied, involving 50 respondents randomly divided into acupuncture and herbal groups. The acupuncture points used were ST 36, ST 40, SP 6, and RN 12, while the herbal group received a red ginseng preparation. Wilcoxon test results for the acupuncture group showed a significant reduction in cholesterol levels (p<0.05). Similarly, the herbal group also showed a significant decrease using Paired T-Test (p<0.05). Both acupuncture and herbal therapies effectively reduced cholesterol levels, with acupuncture showing more pronounced results. These findings support non-pharmacological approaches in managing hypercholesterolemia.